Managing Scarcity: Innovation and Resilience During the COVID-19 Pandemic - Pozzi, Natalie; Zuckerman, Aaron; Son, Joohee; Geraci, Travis C.; Chang, Stephanie H.; Cerfolio, Robert J. (Frontiers in Surgery, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic remains a disruptive force upon the health care system, with particular import for thoracic surgery given the pulmonary pathophysiology and disease implications of the virus. The rapid and severe onset of disease required expedient innovation and change in patient management and novel approaches to care delivery and nimbleness of workforce. In this review, we detail our approaches to patients with COVID-19, including those that required surgical intervention, our expedited and novel approach to bronchoscopy and tracheostomy, and our expansion of telehealth. The pandemic has created a unique opportunity to reflect on our delivery of care in thoracic surgery and apply lessons learned during this time to “rethink” how to optimize resources and deliver excellent and cutting-edge patient care.